(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present investigation was carried out with the objective to identify the most suitable thermal models in relation to evaluation of theoretical productivity of double slope stepped solar still. The productivity of double slope stepped solar still was estimated experimentally and compared with the theoretical productivity calculated with the help of existing thermal models. The highest similarity between experimental and theoretical productivity was achieved by the Dunkle model (1961) followed by the Tsilingiri model (2007) and Rahbar and Esfahani model (2013). It seems that the minimization of the gap between water surface and condensing surface in Double slope stepped solar still resulted in similarity in productivity with Dunkle model.